High Blood Pressure: What You Need to Know - Linda B. Bobroff (EDIS)
High blood pressure, also called hypertension, increases your health risks. If you have high blood pressure, you have a higher chance of getting heart disease or kidney disease or of having a stroke. This 4-page fact sheet was written by Linda B. Bobroff and published by the UF Department of Family, Youth and Community Sciences, October 2012.